Ihtisab (Accountability) in Waqf Institutions: A Review and Synthesis of Literature (Issues in Social and Environmental Accounting (ISEA), 2013)
Waqf is an Islamic philanthropy which has a very big maslahah for the ummah, but less understood by community due to the lack of socialization. Research findings show the weaknesses on accounting and accountability in waqf institutions that reduce waqf maslahah, the lost or dormant of waqf assets. Most of nazhir (trustee) do not manage waqf assets accountably, efficiently, and effectively. In addition, they also do not present it properly in the financial statement and report it to the public. The situation is due to the unavailability of waqf accounting standard for nazhir. This study was conducted with the aim to synthesize the findings of ihtisab (accountability) studies as a basic theory building of accounting standard which is expected to improve performance of nazhir which, in turn,  will increase maslahah of waqf for the ummah. This study employed shuratic method with IIE (Interactive, Integrative and Evolutionary)  process modified by meta-synthesis. The research process was carried out by interactive and integrative of individual findings of the same research topics to find an integrative theory of ihtisab as an evolutionary of Islamic science that is the basic of Ihtisab standard. Synthesizing published 20 ihtisab studies leads some basics of ihtisab standard as guidance for nazhir to be responsible by having good understanding of accounting and conducting dual Islamic accountability. To meet the responsibility, Nazhir should be good in akhlak (moral) and bring his members into a good akhlak too as akhlak is a key success for Islamic institutions. Due to the fact that Synthesis of ihtisab research findings has not been done so far, it is expected that this synthesis of the studies can be the basis for subsequent researchers to continue and develop this findings on the other dimensions of theories and models by developing Islamic science and Islamic empirical methods in line with shariah.